Circularidade das vozes: a poética da cantoria de viola no Ceará - Santos, Maria Elisalene Alves dos (2020)
This thesis is about viola singing and aims to investigate how, nowadays, the poetics of viola singing it is developed in Ceará in its permanent circular movement between the rural and urban area. The study is theoretically based on Zumthor (1993; 2000; 2005; 2010) when he discusses the effect produced in public by the poetic voice and the concept of vocality. Maruschi (1997; 2008; 2010) and Bakhtin (2006) offer support to define orality by analyzing the verses produced by the viola singers and excerpts from their interviews. Alves Sobrinho (2003; 2009), Ayala (1988; 2009; 2015) Cascudo (1978), Castro (2009), Linhares and Batista (1976), Mota (2002), Ramalho (2000), Ribeiro (2009), Santos (2006), Santos (2019), Sautchuck (2012) and Tavares (2009; 2016) contribute to the understanding of the concept of viola singing and the elements that make it up. The period of the field research focuses on the months of August of 2017 to December of 2019. In this interim sound records and audiovisuals of viola singing, of festivals, singing samples and of interviews with the singers of cearense viola are made. After careful analysis of this transcribed material, it is chosen the corpus of this thesis. The result of the research points that the viola singing, while poetics of orality, it is consolidated in the urban area nowadays although the singers prefer to sing in the rural area. In viola singing are found social, regional and group identity traits. The viola singer understands his poetic making as a gift received by God and this gift turns into an aesthetic spectacle and yet in resistance culture. In the process of poetic composition, which consolidates with the effective participation of the public are identified popular themes, varied forms of language, of styles, of sonority and of rhythms in the verses of the viola singers.